ANALISA REKAYASA IKLIM MIKRO MELALUI VARIASI PENAMBAHAN MULSA DAN PUPUK ORGANIK SABUT KELAPA UNTUK BUDIDAYA BAWANG MERAH - Mohamad Solikhin; Wahida Wahida; Yosefina Mangera (Musamus AE Featuring Journal, 2020)
Shallots are a spiced vegetable which, although not native to Indonesia, its use as a culinary delicacy is very close to the tongue of the Indonesian people. Shallots are annual plants in the form of grass, short trunks, and fibrous can reach 15-20 cm high and form clumps. This study aimed to observe the microclimate that occurs around the plant and to observe and assess whether the use of mulch and organic fertilizer could improve the quality and production of shallots. This research was conducted in Sidomulyo Village in August-October 2018. This study used a Randomized Block Design with M0 treatment (without mulch and coconut coir organic fertilizer), M1 (coconut coir organic fertilizer without mulch), M2 (coconut coir organic fertilizer and corn litter mulch), M3 (coconut coir organic fertilizer and rice straw mulch), M4 (coconut coir organic fertilizer and plastic mulch) with three replications. The results showed that the use of rice straw mulch and coconut coir organic fertilizer had better results than other treatments, with an average soil temperature of 29.04 C, air temperature 25.36 C, air humidity 78%, plant ambient temperature 29, 33 C, soil moisture content 66.25, plant height 19.34 cm, number of leaves 18.53, wet tuber weight 9,91 tons/ha, and dry tuber weight 3,80 tons/ha.